Light up the night : America's overdose crisis and the drug users fighting for survival - Lupick, Travis, 1985- (The New Press, 2022)
"A revelatory, moving narrative that offers a harrowing critique of the war on drugs from voices seldom heard in the conversation: drug users who are working on the front lines to reduce overdose deaths"--